Pengaruh terapi bermain pasir warna terhadap tingkat kecemasan pada anak yang mengalami hospitalisasi - Sutrisno Sutrisno; Nathalia Carolina Gerrits (Indonesian Public Health-Observer Information Forum (IPHORR) Kerjasama dengan Persatuan Perawat Nasional Indonesia (PPNI), 2025)
Background: Hospitalization is the admission of an individual to a hospital as a patient for various reasons. Hospitalization can cause excessive anxiety, especially in children, and if left untreated, can reduce the intensity of therapy and care during recovery. One way to reduce anxiety is through play. Play therapy is an important aspect of a child's life and one of the most effective tools for managing stress during hospitalization. Purpose: This study aims to determine the effect of colored sand play therapy on anxiety levels in children hospitalized in the Orchid Room of Dr. Soehadi Prijonegoro Regional Hospital, Sragen. Method: This study used a pre-experimental, one-group pretest-posttest design. The sample consisted of 25 children who received colored sand play therapy. The population in this study were children aged 3-6 years who were treated in the Orchid Room of Dr. Soehadi Prijonegoro Regional Hospital, Sragen, within the past month. A total of 25 children were used for the sample. Statistical analysis used was the Wilcoxon rank test. Results: The anxiety level of hospitalized children before therapy was mostly in the light category, with 21 respondents (84%) and medium category with 4 respondents (16%). After therapy, all respondents experienced light anxiety. The Wilcoxon rank test yielded a p-value of 0.002 (p < 0.05). Conclusion: This study contributes to reducing the anxiety levels of hospitalized preschool children through effective and interactive colored sand play therapy.